Quality of life, supported housing and persons with severe mental disorder: the value of socioeducational perspective on their recovery - García-Pérez, Omar; Fernández García, Carmen María; Inda Caro, María de las Mercedes (Revista Complutense de Educación, 2016)
In the new framework of care for people with severe mental illness (SMI), supported housing becomes a crucial component of socioeducational intervention, noting the positive effects for recovery and improved quality of life. The purpose of this paper is to assess the quality of life of supported housing user´s in Asturias through different instruments and interviews: questionnaire collecting demographic and clinical variables, Social Behavior Schedule (SBS) and Basic Everyday Living Skills (BELS) Community Social Support Questionnaire, Interview Mannheim Social Support and Quality of Life Profile of Lancashire. -LQOLP. The profile of quality of life has been analyzed in terms of socio-clinics variables, personal-social functioning and social and community support. The results show optimal outcomes in safety and leisure activities; on the other hand finances, work, family and health must be improved.  It can also be concluded that people’s quality of life is influenced by the fact of having a work and by their basic and social skills. To sum up, supported housing increases these people’s quality of life, helps to improve their social inclusion and contributes to recover their vital project. A transformational change in the public policy is proposed. Moreover, this change is crucial to emphasize the pedagogical perspective for the integral development and to promote a favorable community environment.
Keywords: quality of life; severe mental illness; supported housing; satisfaction with life; social inclusion